If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Xx + -1ax + -1b = 0 Reorder the terms: -1ax + -1b + xX = 0 Solving -1ax + -1b + xX = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add 'b' to each side of the equation. -1ax + -1b + b + xX = 0 + b Combine like terms: -1b + b = 0 -1ax + 0 + xX = 0 + b -1ax + xX = 0 + b Remove the zero: -1ax + xX = b Add '-1xX' to each side of the equation. -1ax + xX + -1xX = b + -1xX Combine like terms: xX + -1xX = 0 -1ax + 0 = b + -1xX -1ax = b + -1xX Divide each side by '-1x'. a = -1bx-1 + X Simplifying a = -1bx-1 + X Reorder the terms: a = X + -1bx-1
| X(x-3)=130 | | 5X^2+10x^2=0 | | -15=x+24 | | 13+x=-8 | | a+bi=4-bi | | 5x^6=4 | | 5x*2x*x+1= | | 5x(2x)(x+1)= | | 2k+10=22-k | | 3p+3=19-p | | 3x-x+11=21 | | 10s+8-7s=14 | | 7e-4e+5=20 | | 3c+4c+-2=26 | | m^4+2m^2+1=0 | | H=40t^2+4t+10000 | | 6x-18=6x-14 | | 3x^2-24x-7=0 | | 100-5x=2x+5 | | 0.8x-0.2x=10 | | y=1000000+.6*y | | ln(x+1)+ln(x)=2ln(2)+ln(3) | | 2(x+4)+x=50 | | 10+10x*100= | | 10+10*100= | | 2(3x+1)-3(2-x)=41 | | 7x^2-125=1625 | | 32+9y=2y | | 9x^2y^2-12xy+4=0 | | 2x^3-15x^2+42x-44=0 | | 3x+3x=9 | | 6x-12= |